2022
DOI: 10.3758/s13414-022-02498-z
|View full text |Cite
|
Sign up to set email alerts
|

Self-prioritization with unisensory and multisensory stimuli in a matching task

Abstract: A shape-label matching task is commonly used to examine the self-advantage in motor reaction-time responses (the Self-Prioritization Effect; SPE). In the present study, auditory labels were introduced, and, for the first time, responses to unisensory auditory, unisensory visual, and multisensory object-label stimuli were compared across block-type (i.e., trials blocked by sensory modality type, and intermixed trials of unisensory and multisensory stimuli). Auditory stimulus intensity was presented at either 50… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 88 publications
(161 reference statements)
2
6
0
Order By: Relevance
“…Furthermore, our study found that, in Experiment 2, personal distance, in particular, self–friend distance and friend–stranger distance correlated with RT and d′ , respectively, when participants associated abstract quantities with the self or stranger (see ). At the surface, this is in line with previous research which found that a larger personal distance between the self and the stranger affects performance on the matching task (Desebrock, Spence, & Barutchu, 2022; Sui & Humphreys, 2015). However, in this study, the effect of personal distance was not observed when the participants paired the self with specific number symbols.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Furthermore, our study found that, in Experiment 2, personal distance, in particular, self–friend distance and friend–stranger distance correlated with RT and d′ , respectively, when participants associated abstract quantities with the self or stranger (see ). At the surface, this is in line with previous research which found that a larger personal distance between the self and the stranger affects performance on the matching task (Desebrock, Spence, & Barutchu, 2022; Sui & Humphreys, 2015). However, in this study, the effect of personal distance was not observed when the participants paired the self with specific number symbols.…”
Section: Discussionsupporting
confidence: 92%
“…For example, self–friend difference predicted slower RTs specifically to small numbers paired with the self. Similarly, while previous studies found that empathy affects performance on the matching task (Desebrock, Spence, & Barutchu, 2022), no such effect was evident here.…”
Section: Discussionsupporting
confidence: 54%
See 2 more Smart Citations
“…Self-relevance has been demonstrated to confer a performance advantage across a diverse range of experimental tasks (e.g., Cunningham & Turk, 2017; Dalmaso et al, 2019; Desebrock et al, 2022; Golubickis & Macrae, 2021; Macrae et al, 2018; Moray et al, 1959; Rogers et al, 1977; Schäfer et al, 2016; Sui et al, 2013; Woźniak et al, 2018). The matching procedure first introduced by Sui and colleagues (Sui et al, 2012) now provides the standard method for those wanting to investigate the effects of self-relevance without the confounds of stimulus familiarity and overlearning.…”
Section: Self-bias and Lower And Higher Level Representations Of Selfmentioning
confidence: 99%